Damage characteristics of waste engine oil bottom rejuvenated asphalt binder in the non-linear range and its microstructure. (20th June 2018) - Qiu, Yanjun; Ding, Haibo; Rahman, Ali; Wang, Wenqi
Highlights: Comparison study on the damage characteristics of two rejuvenated asphalt binders. Fatigue performance of WEOB is more suitable in thin asphalt pavement layers. DENT test is an effective method to evaluate the physical hardening of asphalt binder. Different performance of regenerated asphalt binder after extended conditioning time. Abstract: This paper aims to compare the damage characteristics of the waste engine oil bottom (WEOB) rejuvenated asphalt binder with aromatic extract oil rejuvenated asphalt binder in the non-linear range. To fulfil this objective, the aged asphalt binder was prepared by aging SBS modified asphalt binder in the laboratory. High temperature, fatigue and low-temperature damage characteristics in the non-linear range were evaluated by conducting multiple stress creep and recovery (MSCR) test, linear amplitude sweep (LAS) test and double edge notched tension (DENT) test, respectively. The microstructure of rejuvenated asphalt binders was characterized by environmental scanning electron microscope (ESEM). The results showed that although the performance of aged asphalt binder can be restored to some extent with two recycling agents, however after conditioning in the bath for 120 h, the two rejuvenated asphalt binders exhibited different ductile states. The microstructure of rejuvenated asphalt binders revealed that WEOB rejuvenated asphalt binder presented a more gelation transition than aromatic extract oil rejuvenated asphalt binder which could be considered as the main reason for the reduction in the ductile performance of WEOB rejuvenated asphalt binder.